Entanglement gain in measurements with unknown results - Zuppardo, Margherita (2019)
We characterize nonselective global projective measurements capable of increasing quantum entanglement between two particles. In particular, by choosing negativity to quantify entanglement, we show that entanglement of any pure nonmaximally entangled state can be improved in this way (but not of any mixed state) and we provide detailed analysis for two qubits. It is then shown that Markovian open system dynamics can only approximate such measurements, but this approximation converges exponentially fast as illustrated using the Araki-Żurek model. We conclude with numerical evidence that macroscopic bodies in a random pure state do not gain negativity in a random nonselective global measurement.